ANALISIS STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN PRODUK BATIK PADA PT. DANAR HADI SURAKARTA - Sri Haryanti; Bambang Mursito; Sudarwati Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2019)
This study aims to find out 1) digital marketing applied by PT Batik Danar Hadi Surakarta, 2) the role of digital marketing in increasing sales of PT Batik Danar Hadi Surakarta, and 3) identifying strengths, weaknesses, opportunities, and threats available using SWOT analysis. The method used in this study is qualitative-descriptive research, namely research based on the strength of analytic descriptions. Data collection is done by interview, observation, and documentation. While data analysis uses SWOT analysis. The results of the study reveals that PT Batik Danar Hadi Surakarta practices digital marketing strategies (online marketing) through social media such as Facebook, instagram, and other internet networks that are connected with wider consumer reach since 2015. PT Batik Danar Hadir cooperates with Zalora, a market place for online media sales that can be accessed globally. The application of digital marketing by PT Batik Danar Hadi can increase sales. This is so because consumers are wider, closer, can check the quality and reputation of the product, and can make transactions online. Keywords: Batik, digital marketing, online, disruption, social networks, quality Keywords: Batik, digital marketing, online, disruption, social networks, quality